Carriage of Staphylococcus aureus among female and male nursing personnel and midwives employed at healthcare centers of Eastern Poland – preliminary report - Paszkiewicz, Justyna; Wrońska, Irena; Plewik, Dorota; Szepeluk, Adam (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Research showed that methicillin-resistant Staphylococcus aureus (MRSA) is the most frequent etiological factor of nosocomial infections. Therefore, improvement of healthcare quality justifies implementation of screening for MRSA carriage among medical personnel, not only among nurses and midwives, but also in auxiliary personnel and physicians. Aim. The aim of this preliminary study was to determine the prevalence of Staphylococcus aureus among nurses and midwives employed at healthcare centers. Material and methods. Swabs from the nasal vestibule and throat were obtained from a total of 50 persons who took part in the screening. The material was inoculated on a selective mannitol agar and incubated at 37ºC for 48 hours. The strains were identified on the basis of their morphology and ability to synthesize free and/or bound coagulase, determined with an aid of Slidex Staph Kit (Biomerieux). Antibiotic susceptibility of the S. aureus isolates was determined with the Kirby-Bauer disc diffusion method, by using cefoxitin (30 μg), clindamycin (2 μg) and erythromycin (15 μg) discs on Mueller-Hinton agar. On the basis of these data, the prevalence of methicillin-resistant S. aureus (MRSA) and the strains representing MLSB resistance phenotype (i.e. showing resistance to macrolides, lincosamides and streptogramin B) was determined. Results and conclusion. We revealed a 44% carriage rate of Staphylococcus aureus in the nasal vestibule and throat of nurses and midwives. MSB and MLSB resistance phenotypes were represented by only one and two isolates, respectively. MRSA were isolated from only 4% of the participants, which is consistent with MRSA carriage rates reported from various regions of the world.